Russian futurist theatre theory and practice - Leach, Robert 1942- (Edinburgh University Press, 2020)
Russian Futurist Theatre explores is the first book to comprehensively uncover the Russian futurist theatre in all its virtuosity and diversity
Title from publisher's bibliographic system (viewed on 12 Nov 2020)
Keywords: Geschichte 1912-1930; Theater / Soviet Union / History / 20th century; Futurism (Music) / Soviet Union; Futurism (Literary movement) / Soviet Union; Theater; Futurismus; Sowjetunion; Russland